First Diagonal Coronary Artery: Left Ventricular Fistula Presenting as Unstable Angina - Murat Sener; Mehmet Akkaya; Muammer Bilici (Case Reports in Cardiology)
Coronary artery fistulae are characterized by communications between a coronary artery and a cardiac chamber or another vascular structure. They are usually congenital, but acquired forms may occur. Most patients are usually asymptomatic. However, some studies have emphasized that the incidence of symptoms and complications increases with age, particularly after the age of 20 (Liberthson et al. 1979, Hong et al. 2004). We aimed to present a very rare form of fistula originating from the first diagonal artery and connecting into the left ventricle.